Space Creating Strategies of Alternative Communities: A Comparative Study of Drop City and Si̇eben Linden Ecovillage - Tuncel, Didem Bedük; EKE, ARMAĞAN SEÇİL MELİKOĞLU (Deniz Yengin, 2021)
According to the United Nations (UN) statistics, more then 55% of the population on earth live in urbanareas. These urban areas are one of the main reasons for increasing global warming and climate crisis.The danger of this crisis will be reduced by increasing the contribution of units forming sustainableliving spaces and common alternative living spaces. In this research, it is aimed to determine thestrategies of man's creation of space by querying through the created alternative living spaces. Thesestrategies, which constitute the essence and originality of the work, are handled within a framework thatextends from the thinking and lifestyle of the community to the possibilities of the environment in whichthe living space is located. In the scope of the study, one of the first alternative communities of the 60'sthat is Drop City and an ongoing eco-village of the 90's that is Sieben Linden Ecovillage samples wereinvestigated through the era they were in, the kind of design trends that effected them, ecologicalprinciples they considered and as a consequence; kind of living spaces they created. The study is doneaccording to combined strategies using case study and logical argumentation research methods together.
Keywords: Space Design Strategy; Ecovillage; Alternative Community; Sustainable Living; Drop City; Sieben Linden Ecovillage